Pengaruh Citra Merek Dan Gaya Hidup Terhadap Sensitivitas Harga - Ella Anastasya Sinambela; Yusuf Rahman Al Hakim; Hendri Dony Hahury (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
Various advancements and dynamics in the business world led to rapid developments in various industries, one of which is the food industry, like Bango soy sauce. With the brand image owned by Bango soy sauce in the marketing world, it’s quite good and follows the trends or lifestyle of it’s consumers, this will prevent any sensitivity to the prices offered. Consumers will still pretend to spend any amount of value to get goods that are in accordance with their perception. The sampling technique in this study using the purposive sampling method and accidental sampling. The combination of the two methods is the selection of samples for anyone who accidentally met and according to criteria set by the researcher. The population in this study were all product users in the City of Gresik and the number was not known with centainty, then a sample of 100 respondents was used. The result show that the brand image has a significant positive influence on the sensitivity of the price of the strok brand sweet soy sauce in Gresik City. The result show that lifestyle has a significant positive effect on the sensitivity of the price of the strok brand sweet soy souce in Gresik City.